The sexual attitude of Malaysian adolescents towards sexual appeal online advertisements - Voon, Shu Shin; Tham, Roger Zhee Zhin; Seah, Chia Jin (2020)
Adolescence is a phase of life where a child grows into an adult. Adolescents have a high sense of curiosity and they are continually developing new traits, behaviors, and skills. The environment that they are exposed to is crucial in shaping their lifestyle. As adolescents nowadays use social media content daily, it is undeniable that they will be exposed to all kinds of advertisements online. Sexual appeal is one of the most common advertising appeals used worldwide. It is widely used in advertising products such as alcoholic drinks, perfume, and lingerie. Nevertheless, there are still debates about whether it is appropriate to use sexual appeal in advertisements as it might affect the behavior of adolescents. Therefore, this research aims to explain the sexual attitude of adolescents towards sexual appeal online advertisements. A total of 10 Malaysian Chinese adolescents from 15-19 years old were interviewed. Research findings indicated that sexual appeal online advertisements do not influence Malaysian adolescents. Moreover, male adolescents have positive attitudes whereas female adolescents have negative attitudes towards the sexual appeal online advertisement. Lastly, sexual appeal online appeals are not effective towards Malaysian adolescents. The research findings help parents have a better understanding of the influence of sexual appeal online advertisement on their children. It also provides insights to advertisers in Malaysia on the perception of Malaysian adolescents towards effectiveness of sexual appeal online advertisements.